Case report: MELAS and T3271C mitochondrial mutation in an adult woman - Chen, Dong-hua; Li, Wei; Jiang, Hai-shan; Yuan, Chao (Frontiers in Neurology, 2023)
Introduction: Patients with mitochondrial disorders always show neurological deficits. However, the diversity of clinical manifestations, genetic heterogeneity and threshold effect caused by maternal heredity make its diagnosis very challenging.Case Presentation: A 30-year-old female presented to our neurology department with a recurrence of symmetrical weakness proximally in the lower extremities. Seven years ago, the patient had a sudden onset of persistent weakness in bilateral proximal lower extremities, along with elevated creatinine kinase (CK) and CK-MB. Given the diagnosis of Guillain-Barre syndrome, she was treated with high-dose glucocorticoid (GC) therapy at the local hospital and recovered. After admission to our hospital, laboratory analysis revealed elevated CK and alpha-hydroxybutyrate dehydrogenase in serum. Electrocardiography showed sinus tachycardia and left high ventricular voltage. Electromyography (EMG) and evoked potential (EP) suggested peripheral neurogenic damage of the upper and lower extremities with myogenic wear. Chronic inflammatory demyelinating polyneuropathy (CIDP) was initially considered, but neurological symptoms were not significantly improved with glucocorticoid shock therapy. An elevated level of lactate was found. The short-tau inversion recovery (STIR) axial magnetic resonance image (MRI) revealed mild hyperintensities, indicating muscle edema. Meanwhile, muscle biopsies suggested pathological changes in mitochondrial disorders (MIDs) and neuronal damage. Further mitochondrial genome analysis revealed a heteroplasmic m3271 T>C mutation in the mitochondrial tRNA-Leu gene (UUR). Collectively, the patient was finally diagnosed with mitochondrial disorder and apparently improved after the corresponding treatment to regulate energy metabolism.Conclusions: To our knowledge, it's the first reports about MELAS with 3271 mutation that have only shown peripheral nerve motion impairment. Proximal weakness is also common in CIDP. In the context of this patient's experience, mitochondrial genome analysis provides an auxiliary criterion for differential diagnosis between MIDs and CIDP. In the meantime, we discussed the clinical effect of GCs on MIDs.